2022
DOI: 10.3390/physchem2020011
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Graphene Nano-Flakes in Materials Chemistry and Astrophysics

Abstract: The elucidation of the mechanism of the chemical evolution of the universe is one of the most important themes in astrophysics. Polycyclic aromatic hydrocarbons (PAHs) provide a two-dimensional reaction field in a three-dimensional interstellar space. Additionally, PAHs play an important role as a model of graphene nanoflake (GNF) in materials chemistry. In the present review, we introduce our recent theoretical studies on the reactions of PAH and GNF with several molecules (or radicals). Furthermore, a hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The binding energies in GNF-K + were lower than those of GNF-Li + and GNF-Na + . However, the values were always higher in energy than 1.0 kcal/mol, which was also higher than the binding energy of H2 to GNF without K. These features indicate that GNF-K + is also possible as a H2 storage [40].…”
Section: Comparison Of Binding Energies In Gnf-m-h2 (M = LI Na and K)mentioning
confidence: 85%
See 1 more Smart Citation
“…The binding energies in GNF-K + were lower than those of GNF-Li + and GNF-Na + . However, the values were always higher in energy than 1.0 kcal/mol, which was also higher than the binding energy of H2 to GNF without K. These features indicate that GNF-K + is also possible as a H2 storage [40].…”
Section: Comparison Of Binding Energies In Gnf-m-h2 (M = LI Na and K)mentioning
confidence: 85%
“…For comparison, the hydrogen adsorption capacity of K + was examined [40]. The binding energy of H2 to GNF-K + is plotted in Figure 7.…”
Section: Comparison Of Binding Energies In Gnf-m-h2 (M = LI Na and K)mentioning
confidence: 99%
“…Previous studies have shown that these levels of theory produce reasonable electronic structures of the carbon systems. [26][27][28][29][30][31] The electronic states of C 60 -PCBM were obtained by natural population analysis and natural bond orbital methods at the CAM-B3LYP/6-31 G(d) level. The binding energy of PCBM to C 60 and E bind are defined as follows:…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Additional calculations were carried out at the same level of theory for Al + , Al 2+ , and Al 3+ systems. We previously investigated interactions between graphene and various molecules using DFT at the same level of theory [ 27 , 28 , 29 , 30 , 31 ]. A similar technique was used for the GR-Al-(H 2 ) n system in this study.…”
Section: Methods Of Calculationmentioning
confidence: 99%